Green information technology for sustainability elicitation in government-based organisations: an exploratory case study - Bokolo, Anthony Jnr; Mazlina, Abdul Majid; Awanis, Romli (Inderscience Enterprises Ltd., 2018)
This study aims to identify the components that influence green IT practice for sustainability elicitation in government-based organisations and further propose a model based on the identified components. The model is verified by adopting case studies by interview and sustainability documents from seven informants in two government-based organisations. Findings from the case studies indicate that organisations propensity to implement green IT practices is based on motivational pressure, practitioners actions, IT governance polices, infrastructures utilised to implement green IT practices which influences sustainability achievement. In addition, findings from this study reveal that government-based organisations in Malaysia are implementing green IT practices to help improve organisational process, effectively decrease IT utilisation cost and also expand organisations opportunities thus heading toward sustainability. Furthermore, this research provides an agenda on how sustainability emerged in government-based organisations through insights from the existing literature and practice-based evidence from the case studies.